The Epoch and Personality of Peter the Great in Nikolay Charykov’s Research - O. A. Chernov (Vestnik MGIMO-Universiteta)
The article reviews the academic contribution of Russian historian and diplomat Nikolay Charykov (1855-1930) to our understanding of the reforms by Peter the Great. In his research, Nikolay Charykov argues that the reforms did not result in a radical break with previous Russia's historical path. He stresses that the cultivation of scientific knowledge and labor skills necessary for modernization started in Russia long before Peter the Great because Russia was part of a European system even before Peter the Great. For example, the author points to Ivan III's marriage to Zoe Palaiologina (Sophia Palaiologina); the employment of captive Livonians by Ivan IV; sending Russian youth to study at Western European universities; Boris Godunov's plans to form a European league of Christian sovereigns. Nikolay Charykov focuses in his studies on the reign of Tsar Alexei Mikhailovich, pointing to his plans to increase the involvement of Westerners in various spheres of life in Russia. Moreover, Nikolay Charykov shows that the personality of the future Emperor was formed under the influence of Russia's increasing interaction with European countries. He concludes that the development of Russia before Peter led to Peter's reforms. He saw the struggle between Sophia and Peter as an interpersonal struggle for power, which in no way violated the primary trend of Russia's development. Peter's reforms became a logical and natural consequence of the previous processes. The merit of Peter was that he successfully continued the previously started transformations by adding to them his character and thinking, which led to the birth of the Russian Empire.